MEMBANGUN LITERASI KEAGAMAAN BAGI PESERTA DIDIK DI MADRASAH - Tubagus Syihabudin; Eneng Muslihah; Siti Ngaisah; Hasbullah (LPPM STAI Muhammadiyah Probolinggo, 2026)
In today's digital era, social patterns among students at MAN 1 and MAN 2 Serang City are no longer limited to the real world but have also expanded into cyberspace. Cyberspace has a powerful force capable of moving people in either a constructive or destructive direction. Unfortunately, it cannot be denied that social interactions among students are now increasingly concerning. One of the main causes of this condition is the low awareness of religious literacy among students. In general, literacy refers to a person's ability to understand and interpret language symbols, both spoken and written. Building religious literacy encompasses two main aspects: reading and writing skills. The main focus of this study is to explore the philosophical aspects that underlie the importance of building religious literacy and to understand its implications in students' lives. This study used a qualitative approach that relies on analysis of library sources. Building religious literacy is a dynamic idea and has a significant impact in various aspects, such as the use of digital media in the classroom and madrasah environments. Therefore, building religious literacy is expected to equip students with various important skills, including critical, visual, media, and multilingual literacy.